LIVING QUR’AN TERHADAP HALAQAH TAHFIZ AL-QUR’AN DI PONDOK PESANTREN AL-MIZAN MUHAMMADIYAH LAMONGAN - Putri Istiqomah; Salamah Noorhidayati (UIN Siber Syekh Nurjati Cirebon, 2021)
Memorizing the Qur’an is a form of reception for the Qur’an. This phenomenon demonstrates the performative function of the Qur’an outside the text. The purpose of this study was to determine the practice of Halaqah Tahfiz al-Qur’an activities and the form of treatment or reception of students of Al-Mizan Muhammadiyah Lamongan in the Halaqah activity. This research resulted in the knowledge that the activities of Halaqah Tahfiz al-Qur’an in Islamic boarding schools are compulsory and superior activities that become a vehicle and means of regeneration for students. The forms of treatment of students in the Halaqah Tahfiz al-Qur’an activities include: ablution before activities, praying, praying Hifz al-Qur’an, praying hajat, writing memorized verses, and muroja'ah. The meaning produced from the Halaqah Tahfiz al-Qur’an activity follows the sociological theory of knowledge by Karl Mannheim including the objective meaning, the Halaqah Tahidz Qur’an activity is a compulsory and superior program initiated directly by KH. Drs. Sutaman and must be followed by all students who live there. As for the expressive meaning, the activities of the Halaqah tahfiz al-Qur’an bring benefits according to the way they treat the Qur’an. As for the meaning of documentary, the Halaqah Tahfiz al-Qur’an activity is an activity without coercion and purely from the wishes of the students themselves, supported also by the motivation they get from themselves, their parents, and the Islamic boarding school caretakers. This research resulted in a new understanding and contribution reception package for the Living Qur’an research.